2019
DOI: 10.1200/jco.2019.37.15_suppl.3501
|View full text |Cite
|
Sign up to set email alerts
|

Prospective pooled analysis of four randomized trials investigating duration of adjuvant (adj) oxaliplatin-based therapy (3 vs 6 months {m}) for patients (pts) with high-risk stage II colorectal cancer (CC).

Abstract: 3501 Background: 6m of oxaliplatin-based treatment is an option as adj chemotherapy for patients with high risk stage II CC (T4, inadequate nodal harvest, poorly differentiated, obstruction, perforation or vascular/perineural invasion). The IDEA collaboration showed shorter treatment duration to be appropriate for most pts with stage III colon cancer. The results of the 4 IDEA studies with stage II pts are presented here. Methods: A prospective, pre-planned pooled analysis of high-risk stage II patients from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 0 publications
3
44
0
2
Order By: Relevance
“…It is also felt by the panel members that patients with high risk, patients with pT4 and/or <12 lymph nodes or accumulation of several intermediate risk factors, might be considered for the addition of oxaliplatin therapy based on a trend to an increased benefit, although this did not achieve statistical significance in the stage II high-risk subgroup analysis of the MOSAIC trial [I, B]. 72 For this high-risk population, the IDEA trial explored the optimal duration of the oxaliplatin-based adjuvant treatment, finding identical results to those reported for stage III patients, a non-proven non-inferiority for 3 months of treatment and there was a proven non-inferiority of CAPOX and inferiority of FOLFOX for 3 months when compared with 6 months of FOLFOX, 82 with all the limitations of these post hoc analyses as stated before. The presence of MSI/MMR in Annals of Oncology localised disease confers better prognosis and less benefit to adjuvant therapy so chemotherapy should be indicated with caution and always in combination with oxaliplatin 51e55 (see Figure 4 for integration of clinicopathological and molecular factors with therapeutic recommendations).…”
Section: Stage II Diseasementioning
confidence: 99%
“…It is also felt by the panel members that patients with high risk, patients with pT4 and/or <12 lymph nodes or accumulation of several intermediate risk factors, might be considered for the addition of oxaliplatin therapy based on a trend to an increased benefit, although this did not achieve statistical significance in the stage II high-risk subgroup analysis of the MOSAIC trial [I, B]. 72 For this high-risk population, the IDEA trial explored the optimal duration of the oxaliplatin-based adjuvant treatment, finding identical results to those reported for stage III patients, a non-proven non-inferiority for 3 months of treatment and there was a proven non-inferiority of CAPOX and inferiority of FOLFOX for 3 months when compared with 6 months of FOLFOX, 82 with all the limitations of these post hoc analyses as stated before. The presence of MSI/MMR in Annals of Oncology localised disease confers better prognosis and less benefit to adjuvant therapy so chemotherapy should be indicated with caution and always in combination with oxaliplatin 51e55 (see Figure 4 for integration of clinicopathological and molecular factors with therapeutic recommendations).…”
Section: Stage II Diseasementioning
confidence: 99%
“…Three months of CAPOX is replacing the 6 months of adjuvant FOLFOX for a considerable number of patients. More recent data also show a possible reduction in the length of adjuvant treatment in high-risk stage II patients [13]. Here, we describe the characteristics of eight patients who presented life-threatening enterocolitis after adjuvant CAPOX.…”
Section: Discussionmentioning
confidence: 84%
“…In the overall population, 6 months was superior to 3 months, however, 3 months of CAPOX regimen was non-inferior to 6 months. There were 1254 patients with high risk stage II disease in the IDEA collaborative study (including TOSCA study) which investigated the optimal duration of adjuvant therapy [56]. Investigators concluded that 3 months of CAPOX may be non-inferior to 6 months in high risk stage II cancers, reflecting the finding in stage III disease.…”
Section: Duration Of Therapymentioning
confidence: 99%